Fabrication of poly(vinyl alcohol)-Carrageenan scaffolds for cryopreservation: Effect of composition on cell viability. (20th August 2016) - Chopra, Pankaj; Nayak, Debasis; Nanda, Arpita; Ashe, Sarbani; Rauta, Pradipta Ranjan; Nayak, Bismita
Highlights: PVA-Carrageenan scaffolds were prepared via freeze-gelation technique. 3 dimensional highly porous, interconnected lamellar structure observed in SEM. All the scaffold constructs were found to be hemocompatible. The scaffolds exhibited excellent cell viability after 15 days of cryopreservation. Abstract: The present investigation reports the fabrication of three dimensional (3D), interconnected, highly porous, biodegradable scaffolds using freeze-gelation technique. The hydrogels prepared with different ratios (5:5, 6:4, 7:3, 8:2 and 9:1) of poly(vinyl alcohol) (PVA) and Carrageenan (Car) was lyophilized to obtain their respective scaffolds. The PVA-Car scaffolds were further characterized by scanning electron microscopy (SEM), X-ray diffraction (XRD) and attenuated total reflectance-Fourier transform infrared spectroscopy (ATR-FTIR). The prepared scaffolds were found to be biodegradable and highly compatible with hemoglobin. Further, normal keratinocyte (HaCaT) and osteosarcoma (Saos-2) cells seeded on PVA-Car scaffolds were cryopreserved for 15 days and their viability was checked at regular interval of 3 days (0, 3, 6, 9, 12, 15 days) through MTT assay and fluorescence microscopy. Overall, the collective results indicate the scaffold constructs with 7:3 and 8:2 PVA-Car ratios possess ideal characteristics for tissue engineering applications and for long term cryopreservation of cells.